Sun & moon sisters - Le, Khoa, 1982- (Insight Kids, 2016)
"Two sisters, the Sun and the Moon, rule the sky, but each is jealous of the other's power. One night, to settle their quarrel, they decide to switch roles--and calamity ensues"--Amazon.com.